2016
DOI: 10.1111/inm.12257
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory investigation of sexual health screening in the first 12 weeks of case management in populations with severe mental illness

Abstract: The sexual health of people with mental illness is commonly overlooked, neglected or inadequately addressed in mental health care, despite evidence showing that people with severe mental illness are more vulnerable to sexually transmitted infections (including HIV), sexual side-effects, and sexual dysfunction than the general population. This article reports a study that investigated sexual health screening in five community mental health clinics within a large a regional health service in Victoria, Australia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
(132 reference statements)
0
3
0
1
Order By: Relevance
“…The sexual health of people with SMI is commonly overlooked, neglected, or inadequately addressed in mental healthcare, despite evidence showing that they are more vulnerable to sexually transmitted infections (including HIV), sexual side effects from prescribed medications, and sexual dysfunction than the general population. A recent examination of 186 medical records showed that less than 40% of patients with SMI were provided with sexual health screening during their first 12 weeks of case management [30]. The study also found that screening for sexual side effects and issues of fertility, sexual self-esteem, safer sexual practices, and sexual dysfunction were rarely carried out.…”
Section: Recovery Approach To Sexual Healthmentioning
confidence: 99%
“…The sexual health of people with SMI is commonly overlooked, neglected, or inadequately addressed in mental healthcare, despite evidence showing that they are more vulnerable to sexually transmitted infections (including HIV), sexual side effects from prescribed medications, and sexual dysfunction than the general population. A recent examination of 186 medical records showed that less than 40% of patients with SMI were provided with sexual health screening during their first 12 weeks of case management [30]. The study also found that screening for sexual side effects and issues of fertility, sexual self-esteem, safer sexual practices, and sexual dysfunction were rarely carried out.…”
Section: Recovery Approach To Sexual Healthmentioning
confidence: 99%
“…Unsafe sex has been ranked the second leading global risk for burden of disease in the world; with almost three quarters of the global burden of unsafe sex occurring in sub-Saharan Africa (12). Unfortunately, the majority of psychiatric care services for SMI in sub-Saharan Africa do not routinely assess for and manage RSB, making People with SMI more likely to engage in high-risk sexual behavior and putting them at risk of poorer sexual health outcomes (13,14,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…The need for training to increase their competence was greatly expressed by health workers though they were not sure how sexuality issues would be incorporated in MH services, their roles and the extent to which health management would be supportive [ 37 ]. Furthermore, studies show that SRH of people with MI is rarely assessed in psychiatric health facilities [ 38 42 ]. For instance, only 37% of youth admitted in a Canadian psychiatric hospital had SRH assessment documented [ 41 ].…”
Section: Introductionmentioning
confidence: 99%